Investigation of distribution uniformity of distributor for biogas slurry application based on CFD analysis - Fu, Jingjing; Chen, Yongsheng; Xu, Binxing; Ma, Biao; Wang, Pengjun; Wu, Aibing; Chen, Mingjiang (International Journal of Agricultural and Biological Engineering, 2023)
A horizontal distributor for biogas slurry application was proposed to explore the distribution performance through CFD analysis and verified by field test. The rheological properties of biogas slurry were analyzed at first, and key parameters were obtained for the next simulation. The effects of distribution modes, inlet direction, and outlets number on the velocity distribution of flow field and mass flow rate of the horizontal distributor were investigated by CFD simulations. Results of rheological properties indicated that biogas slurry was a non-Newtonian fluid and exhibited shear-thinning behavior. It can be well described by power-law model. The simulation results showed that the geometry of rotor, especially the block numbers was the main factor that determined the fluid movement and trajectory of distribution and output. The mode rotor 1 with two blocks reached the lowest variable coefficient of mass flow rate (4.49%), indicating a higher degree of uniformity. The upward inlet direction would obtain less dead zone, and the distributor with an even outlets number would possess more uniform distribution and less dead zone. The field test of the distributor with rotor 1, upward inlet direction, and 24 outlets has been carried on to verify the simulation results, the variable coefficient of mass flow was 13.06%, which was slightly higher than the simulation (9.23%), but it still within the range of requirement (<15%). The proposed model and the findings of this work are of guiding significance for the study of the utilization technology and equipment of liquid biogas residue.Keywords: distributor, biogas slurry, distribution uniformity, rheological properties, CFDDOI: 10.25165/j.ijabe.20231601.7460Citation: Fu J J, Chen Y S, Xu B X, Ma B, Wang P J, Wu A B, et al. Investigation of distribution uniformity of distributor for biogas slurry application based on CFD analysis. Int J Agric & Biol Eng, 2023; 16(1): 45–52.